Information and Communications Technology Retooling Program: Optimizing Teachers’ Competency - Roque, Jerwin C.; Santos, Joseline M. (Future Science / FSH-PH Publications, 2024)
The main purpose of this study is to evaluate the ICT retooling program for teachers and its influence on their competency and performance. A research-made questionnaire was distributed to 260 Junior High School teachers in Bulacan District II, including Baliwag, Bustos, and Plaridel. Additionally, School Principals, Master Teachers, Head Teachers, and Education Program Supervisors in Bulacan were evaluated using a modified research questionnaire. The findings revealed that teachers viewed the ICT Retooling Program positively, noting its encouragement of participation and diverse perspectives rather than a sole focus on technical skills. However, this led to relatively low post-program enthusiasm for educational innovation. Teachers rated themselves competent in ICT, excelling in knowledge creation, deepening, and acquisition dimensions, and demonstrated proficiency in utilizing ICT for teaching and learning, particularly in positive ICT use criteria. The study concluded that a balance between soft skills development (confidence, assertiveness, networking) and technical skills is necessary to foster innovation in education. Continuous professional development in ICT is crucial for translating policy directives into classroom actions and creating inclusive learning environments. Recommendations include conducting a needs assessment to identify areas for improvement in teachers' ICT skills and aligning ICT retooling programs with broader school improvement goals. These recommendations should be integrated into the school improvement plan for increased effectiveness. A long-term sustainability plan, including continuous professional development and technology integration, is essential. Financial aid for graduate degree programs should be provided to sustain teacher competency. Lastly, the Sobel Test is recommended to measure the significance of the teachers' ICT Competency Framework (CFT) and PPST results in the ICT retooling program.